2021
DOI: 10.18203/2394-6040.ijcmph20211245
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge attitude and practices regarding mask usage during COVID-19 pandemic in general population of India: a qualitative study

Abstract: Background: Facemasks are recommended to control the COVID-19 pandemic transmission. This study was conducted with a purpose to investigate the knowledge, attitude and practices among general population regarding the usage of facemask during COVID-19 pandemic to limit the spread of the corona virus disease.Methods: A cross sectional study was conducted through Google forms. Questionnaire consisted of 7, 3 and 5 questions on knowledge, attitude and practices respectively. Questionnaire was shared on social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…This indirectly reflects that the study population were aware of how bad the COVID-19 infection is and had a good attitude towards preventing spread/contacting the disease. Observations of the present study were in line with observations among adults from different Indian states made by Sayaware et al where 97.6% of the study participants had good attitude towards face mask use during pandemic 13 . On the other hand, a rural population-based study by Harshal Kawanpure et al in Madhya Pradesh 17 showed mask acceptance (87.3%) slightly less compared to our study (98.6%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This indirectly reflects that the study population were aware of how bad the COVID-19 infection is and had a good attitude towards preventing spread/contacting the disease. Observations of the present study were in line with observations among adults from different Indian states made by Sayaware et al where 97.6% of the study participants had good attitude towards face mask use during pandemic 13 . On the other hand, a rural population-based study by Harshal Kawanpure et al in Madhya Pradesh 17 showed mask acceptance (87.3%) slightly less compared to our study (98.6%).…”
Section: Discussionsupporting
confidence: 92%
“…The appropriate use, storage and cleaning or disposal of masks are essential to make them as effective as possible 4 . Lack of proper knowledge and skill set for use, among common man, especially in developing countries, has led to inappropriate use of face mask 13 . This gives them a false sense of safety and breeches the prevention measures leading to the spread of the COVID-19 disease 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Which is similar to a study conducted by Bhawna Sayare, wherein the mean knowledge score was higher among female participants (5.07%) as compared to male participants (4.93%) and the difference was statistically significant. [13] But in studies conducted by Howard M C and by Mitrokhin, though the men were less likely to wear face mask no significant gender differences were noted. [14,9] It was also noted that there was significant association among practice and academic year of the study participants (p =0.03, at 95% CI and F-value = 2.64),this finding is similar to finding of our current study.…”
Section: Discussionmentioning
confidence: 89%